GAMBARAN KEBERSIHAN GIGI PADA SISWA SEKOLAH DASAR LUAR BIASA BINTORO KABUPATEN JEMBER TAHUN 2008 - Kiswaluyo Kiswaluyo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
Students of schools for disabled are more highly risky to have poor dental hygiene condition than that of the normal ones. They need more attention in order to possess the same condition as normal children. The present study animed at knowing the dental hygiene of students in elementary school for disabled in Bintoro District Jember Regency. The Approach used was cross-sectional. The result shows that there is no correlation between genders and classes existed and student’s dental hygiene.